ĐA DẠNG SINH HỌC THỰC VẬT PHÙ DU Ở VÙNG HẠ LƯU SÔNG VÀM CỎ, TỈNH LONG AN - Lê, Thị Trang; Phan, Doãn Băng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
BIODIVERSITY OF PHYTOPLANKTON IN THE LOWER OF VAM CO RIVER, LONG AN PROVINCE The study was conducted at ten sites in the lower of Vam Co river, Long An province from January to July 2018. The samples were collected by phytoplankton net and fixed with 5% formalin at the field. A total of 223 phytoplankton species were recorded, belonging to 106 genera, 66 families, 37 orders, and 6 divisions, of which the diatom group dominated in the species number. The average cell density ranged from 27 144 ± 8 508 cells/liter to 153 743 ± 45 300 cells/liter. The dominant species recorded in the study area include Merismopedia punctata, Oscillatoria acuta, Oscillatoria perornata, Oscillatoria sp., Microcystis aeruginosa, Microcystis panniformis, Lyngbya martensiana, Cyclotella meneghiniana, Skeletonema costatum, Coscinodiscus jonesianus, Melosira granulata. The high densities of phytoplankton were rich food sources for larvae, zooplankton, shrimp, fish, and bivalves. The Shannon - Weiner index, Simpson index, and Margalef index showed that the phytoplankton of lower Long An was diverse and abundant.